1996
DOI: 10.1007/s001250050516
|View full text |Cite
|
Sign up to set email alerts
|

[13C]0ctanoic acid breath test for non-invasive assessment of gastric emptying in diabetic patients: Validation and relationship to gastric symptoms and cardiovascular autonomic function

Abstract: Since there is a need for a widely applicable non-invasive test to assess gastric emptying in diabetic patients, we evaluated the sensitivity, specificity, and reproducibility of the [13C]octanoic acid breath test as compared with scintigraphy. Moreover, we examined the relationship between the breath test indices and gastric symptoms, cardiovascular autonomic function, and metabolic parameters. Forty healthy control subjects and 34 diabetic patients were studied. Three indices of gastric emptying, assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
111
3
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 36 publications
13
111
3
4
Order By: Relevance
“…However, it has been reported that examination of autonomic nervous functions and glycosylated hemoglobin are not useful for predicting the occurrence of diabetic gastroparesis (10)(11)(12), and that the manifestation of subjective symptoms is not significantly correlated with the severity of visceral neuropathy. Other studies, however, have reported that the occurrence of diabetic gastroparesis was closely related to the results of heart rate variability analysis (13,14). These findings suggest that the treatment of diabetic gastroparesis should be initiated from the early stage and before the appearance of subjective symptoms, based on the results of an easy and simple assessment of gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it has been reported that examination of autonomic nervous functions and glycosylated hemoglobin are not useful for predicting the occurrence of diabetic gastroparesis (10)(11)(12), and that the manifestation of subjective symptoms is not significantly correlated with the severity of visceral neuropathy. Other studies, however, have reported that the occurrence of diabetic gastroparesis was closely related to the results of heart rate variability analysis (13,14). These findings suggest that the treatment of diabetic gastroparesis should be initiated from the early stage and before the appearance of subjective symptoms, based on the results of an easy and simple assessment of gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 94%
“…However, Nakamuraet al (13) reported that coefficients of variation (CVr.r) obtained by time-domain analysis of heart rate variability were closely correlated with gastric motility evaluated by the acetoaminophen and isotope methods. Furthermore, Ziegler et al (14) reported that gastric motility evaluated by the [13C]octanoic acid breath test was correlated with dysautonomia evaluated by CVR-R.However, few studies have reported on the relationship betweenthe spectral analytical parameters of heart rate variability and gastric motility. In the present study, HF power, an index of parasympathetic nerve functions, was significantly correlated with peak power values of EGGand gastric motility at a frequency between 2.4 and 3.6 cpm.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies using scintigraphic techniques to measure gastric emptying have shown delayed gastric emptying in patients with diabetes varying from 30 to 60% (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). However, there are several important limitations to these studies.…”
mentioning
confidence: 99%
“…The 13 C-octanoic acid breath test is a valid and well-reproducible method to measure gastric emptying [13][14][15]. It has been shown that gastric emptying measured by breath tests correlated well with scintigraphic studies [6,13,16]. Breath sample collection for the 13 CO 2 breath test does not inconvenience patients and can be performed even in patients with advanced disease.…”
Section: Discussionmentioning
confidence: 99%